Grapes and Wines - Advances in Production, Processing, Analysis and Valorization 2018
DOI: 10.5772/intechopen.72799
|View full text |Cite
|
Sign up to set email alerts
|

Convenience of Applying of Viticulture Technique as a Function of the Water Status of the Vine-Stock

Abstract: This study determined the effect that the irrigation dosage and cluster thinning showed over the antioxidant activities and total phenols in grapes, and phenolic profile and chromatic characteristics of cv. Tempranillo wines. The experiment was carried out over two consecutive seasons at an experimental vineyard in Extremadura (Spain). The plants were subjected to two post-véraison irrigation treatments, one at 100% (R100) and the other at 25% (R25) of crop evapotranspiration (ETc). Two crop loads (C and T) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 86 publications
2
8
0
Order By: Relevance
“…Graciano grown in plastic pots, irrigated with sustained deficit irrigation (SDI), Niculcea et al found registered decreases in FLAVO and increases in CA in respect to non-irrigated grapes [ 40 ]. In Tempranillo vines grown in the same edaphoclimatic conditions as the present work, Gamero et al [ 83 ] found increases in Pro B1 and Pro B3 dimers in irrigated grapes. When regulated deficit irrigation (RDI) was applied to ‘Monastrell’ grapevines grown in eastern Spain under semiarid conditions, the content of EC in these grapes was mainly flavanol, and epicatechin-3-gallate decreased [ 108 ].…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Graciano grown in plastic pots, irrigated with sustained deficit irrigation (SDI), Niculcea et al found registered decreases in FLAVO and increases in CA in respect to non-irrigated grapes [ 40 ]. In Tempranillo vines grown in the same edaphoclimatic conditions as the present work, Gamero et al [ 83 ] found increases in Pro B1 and Pro B3 dimers in irrigated grapes. When regulated deficit irrigation (RDI) was applied to ‘Monastrell’ grapevines grown in eastern Spain under semiarid conditions, the content of EC in these grapes was mainly flavanol, and epicatechin-3-gallate decreased [ 108 ].…”
Section: Discussionsupporting
confidence: 75%
“…Touriga Nacional during three seasons in the Douro region, they observed increases in KpG, My-hexoside, QcG, KpR and QcGR in two of the three vintages, while MyG decreased only in two of them. Gamero et al [ 83 ], in wines elaborated from vines grown in similar edaphology and climatic conditions to those in the present work, reported a different irrigation effect depending on whether the wines were created from thinned or control vines. However, little or no change was noticed for other flavonoid compounds.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…Therefore, anthocyanins are the main agents responsible for the red wine color. These substances are able to react with compounds extracted from wood but also with other compounds formed by redox potential changes, induced by wood components [ 60 ].…”
Section: Resultsmentioning
confidence: 99%